VESTIBULER DISORDERS AND VESTIBULER REHABILITATION - Arzu Susin,; Zeliha Ünlü, (Archives of Rheumatology, 2004)
There's a growing evidence about the efficiency of the vestibuler rehabilitation in the patients with peripheral vestibuler disorders and other conditions causing vertigo. Therapeutic exercises for the head and eyes and balance exercises help the functional recovery in these patients. Functional recovery is much more better in the patients with peripheral vestibuler disorders. However there is noticeable functional recovery in the patients with vertigo due to central etiology albeit complete recovery is rare.